Geoheritage conservation of paleontological sites in Aring Area, Gua Musang District, Kelantan, Malaysia - Dony Adriansyah Nazaruddin; Ahmad Rosli Othman (Insight, 2014)
Many small invertebrate fossils have been recently discovered in two locations in Aring area, Gua Musang district,